The fucose-binding lectin from Ralstonia solanacearum. A new type of beta-propeller architecture formed by oligomerization and interacting with fucoside, fucosyllactose, and plant xyloglucan - Kostlánová, Nikola; Mitchell, Edward P; Lortat-Jacob, Hugues; Oscarson, Stefan; Lahmann, Martina; Gilboa-Garber, Nechama; Chambat, Gérard; Wimmerová, Michaela; Imberty, Anne (The Journal of biological chemistry, 2005)
Plant pathogens, like animal ones, use protein-carbohydrate interactions in their strategy for host recognition, attachment, and invasion. The bacterium Ralstonia solanacearum, which is distributed worldwide and causes lethal wilt in many agricultural crops, was shown to produce a potent L-fucose-binding lectin, R. solanacearum lectin, a small protein of 90 amino acids with a tandem repeat in its amino acid sequence. In the present study, surface plasmon resonance experiments conducted on a series of oligosaccharides show a preference for binding to alphaFuc1-2Gal and alphaFuc1-6Gal epitopes. Titration microcalorimetry demonstrates the presence of two binding sites per monomer and an unusually high affinity of the lectin for alphaFuc1-2Gal-containing oligosaccharides (KD = 2.5 x 10(-7) M for 2-fucosyllactose). R. solanacearum lectin has been crystallized with a methyl derivative of fucose and with the highest affinity ligand, 2-fucosyllactose. X-ray crystal structures, the one with alpha-methyl-fucoside being at ultrahigh resolution, reveal that each monomer consists of two small four-stranded anti-parallel beta-sheets. Trimerization through a 3-fold or pseudo-3-fold axis generates a six-bladed beta-propeller architecture, very similar to that previously described for the fungal lectin of Aleuria aurantia. This is the first report of a beta-propeller formed by oligomerization and not by sequential domains. Each monomer presents two fucose binding sites, resulting in six symmetrically arranged sugar binding sites for the beta-propeller. Crystals were also obtained for a mutated lectin complexed with a fragment of xyloglucan, a fucosylated polysaccharide from the primary cell wall of plants, which may be the biological target of the lectin.
Keywords: sekvenční homologie aminokyselin; vazebná místa; Arabinose; trisacharidy; Time Factors; terciární struktura proteinů; rekombinantní proteiny; Carbohydrate Conformation; Amino Acid Sequence; senzitivita a specificita; lektiny; Ligands; fukosa; genetické vektory; sacharidové sekvence; Protein Conformation; kalorimetrie; sekundární struktura proteinů; Calorimetry; Trisaccharides; Epitopes; Surface Plasmon Resonance; vodíková vazba; Sequence Homology, Amino Acid; Fucose; vazba proteinů; časové faktory; Molecular Sequence Data; dimerizace; glukany; Ralstonia solanacearum; Temperature; Protein Structure, Secondary; molekulární modely; Cloning, Molecular; buněčná stěna; epitopy; Crystallography, X-Ray; diterpeny; Protein Binding; kinetika; Cell Wall; ligandy; Diterpenes; povrchová plasmonová rezonance; sekvence aminokyselin; Lectins; Recombinant Proteins; Mutation; oligosacharidy; Models, Molecular; konformace sacharidů; molekulární sekvence - údaje; Hydrogen Bonding; Thermodynamics; konformace proteinů; klonování DNA; termodynamika; Genetic Vectors; Polysaccharides; Binding Sites; mutace; Disaccharides; Dimerization; Carbohydrate Sequence; Kinetics; xylany; Protein Structure, Tertiary; teplota; arabinosa; disacharidy; polysacharidy; Sensitivity and Specificity; krystalografie rentgenová; Oligosaccharides; Xylans; Glucans